Earth's energy imbalance since 1960 in observations and CMIP5 models. Issue 4 (19th February 2015) - Smith, Doug M.; Allan, Richard P.; Coward, Andrew C.; Eade, Rosie; Hyder, Patrick; Liu, Chunlei; Loeb, Norman G.; Palmer, Matthew D.; Roberts, Chris D.; Scaife, Adam A.
Abstract Observational analyses of running 5 year ocean heat content trends (Ht) and net downward top of atmosphere radiation (N) are significantly correlated (r 0.6) from 1960 to 1999, but a spike in Ht in the early 2000s is likely spurious since it is inconsistent with estimates of N from both satellite observations and climate model simulations. Variations in N between 1960 and 2000 were dominated by volcanic eruptions and are well simulated by the ensemble mean of coupled models from the Fifth Coupled Model Intercomparison Project (CMIP5). We find an observation‐based reduction in N of − 0.31 ± 0.21 W m−2 between 1999 and 2005 that potentially contributed to the recent warming slowdown, but the relative roles of external forcing and internal variability remain unclear. While present‐day anomalies of N in the CMIP5 ensemble mean and observations agree, this may be due to a cancelation of errors in outgoing longwave and absorbed solar radiation.